TEACHER-INITIATED PRE-EMPTIVE FOCUS ON FORM AND LEARNER UPTAKE IN COMMUNICATIVE ENGLISH CLASSES: A case study at an SMP in Bandung - Hamidy, Mahmud Fauzi (2009)
This study investigates one phenomenon in classroom practice wherein a teacher introduces grammar to students during communicative English activities, i.e. teacher-initiated pre-emptive focus on form (TIPFF). Besides, it also investigates the students' responses which come after the grammar information is given by teacher, i.e. learner uptake. Three research problems were formulated, i.e. 'the context of classroom interaction in which teacher initiates pre-emptive focus on form (PFF)', 'the way teacher introduces grammar to students in PFF episodes', and 'the way learner uptake is triggered in teacher-initiated PFF episodes'. A qualitative method of inquiry is used as the design of this study. The data was collected by classroom observations in communicative English classes of a Junior High School in Bandung. One English teacher and fifty students from two English classes were involved as the participants of this study. Parts of the classroom interaction which contain the discussion of grammar were identified as PFF episodes. For the first research problem, this study identifies five contexts of interaction in which the teacher initiated PFF. For the second research problem, it is found that the ways the teacher taught grammar to the students were both deductive and inductive by involving the dimensions meaning and form of grammar, without involving the dimension use. For the last research problem, the finding reveals that how learner uptake was triggered depends on how grammar was taught. The answer to the third research problem appears to provide reason why the amount of learner uptake is higher in student-initiated PFF than in teacher-initiated PFF, as reported by Ellis et al. (2001).